DESENVOLVIMENTO DO ABACAXIZEIRO VARIEDADE TURIAÇU SUBMETIDO A ADUBAÇÃO COM NÍVEIS DE NITROGÊNIO E POTÁSSIO EM TERRA FIRME DA AMAZÔNIA CENTRAL - Souza de Lima, Erivan (Instituto Nacional de Pesquisas da Amazônia - INPA, 2024)
The pineapple crop is second in production value among temporary crops in Amazonas. The Turiaçu variety predominates in commercial plantations in the State, however, there is little agronomic research carried out with the variety in local conditions and the productivity of the plantations is low in relation to the national average. The adequate fertilization is one of the gaps in the production system. The nutrients N and K are the most required by the crop and have a great influence on fruit productivity and quality. There are no fertilization recommendations based on studies carried out with the Turiaçu variety in local conditions, therefore, the hypothesis of this experiment is that it is possible to obtain gains in productivity and fruit quality by recommending adequate doses of these nutrients for soil fertilization. The objective of this study was to evaluate the effect of N and K doses on plant development and fruit production and quality of the Turiaçu variety cultivated in Amazonas. The experiment was conducted in the Experimental Field of Embrapa Amazônia Occidental, Manaus, AM, using a complete randomized block design in a factorial scheme with three doses of N (7.5; 15 and 22.5 g plant-1) and five doses of K (7.5; 15; 22.5; 30 and 45 g plant-1) with three replications. The effects of treatments on nutrient content and chemical characteristics of the soil, nutrient content in plant leaves, number of leaves (NF), width (LFD) and length (CFD) of leaf D, plant height (AP), fruit mass with (MFCC) and without crown (MFSC) and total soluble solids content (TSS) in fruit juice. With an increase in the N dose, there was a reduction in pH and base saturation and an increase in the Al content and aluminum saturation in the soil. The K and Na contents in the soil increased linearly with the increase in the K dose. The Cu and Mn contents in leaf D increased with the application of higher doses of N, while the Fe content reduced. The highest concentration of K in leaf D, according to the estimation using quadratic regression, will be obtained with the application of 20.2 g of K plant-1. The Ca content in leaf D decreases linearly with the increase in the K dose. With the increase in the K dose, there is a reduction in the Mg content in leaf D with a tendency for the concentration to stabilize when higher doses are used. The Fe content in leaf D increased linearly with increasing K dose, however, this effect was only observed when the lowest N dose was used (7.5 g plant-1). The fertilization with N had an effect on NF, CFD, LFD and AP, whereas K did not influence any of these characteristics. The increase in the dose of N promoted an increase in CFD and AP, regardless of the dose of K. The increase in LFD as a function of the dose of N ocurred only when using the highest doses of K (30.0 and 45.0 g plant-1). Under the conditions that the experiment was carried out, doses of N and K used in fertilization did not influence the productivity or physical characteristics of the fruit. Experimental conditions may have contributed to no significant effects of the treatments on productivity and physical characteristics of the fruits. However, high productivity was obtained regarding number and mass of fruits produced in relation to the average productivity nationally, of the Amazonas and the municipality of Itacoatiara, but with classification by size and weight of fruit in intermediate quality classes. Doses of N can reduce or increase the TSS content, depending on the K dose used, however, the values obtained are high (14.5 to 15.8 ºBrix) and lie in a range within which there is no difference of market value.
Keywords: Ananas comosus (L.) Merril; Nutrição mineral; Produção de frutos; Qualidade de fruto